Studi Perbandingan Tekstur dan Cita Rasa Brownies Kukus dan Panggang Berbasis Tepung Mocaf dan Tepung Gandum Hitam - Amanda Meylan Zatu Ghassani; Alip Suroto; Ida Ayu Kade (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Public demand for healthy, low-gluten and high-fiber food products encourages innovation in the bakery industry. This study aims to compare the texture and taste of brownies based on mocaf flour (Modified Cassava Flour) and rye flour with steamed and baked processing methods, and determine the formulation that has the best organoleptic quality. Mocaf flour was chosen because it is gluten-free, low glycemic index and locally sourced, while rye flour is rich in fiber, anthocyanin and antioxidant pigments and is beneficial for health. This study used an experimental design with three variations of mocaf proportions: rye (75:25, 50:50, 25:75) and two processing methods. Hedonic organoleptic tests were conducted by 36 panelists on aroma, taste, texture and overall reception on a likert scale of 1-7. The results showed that the processing method and the proportion of flour had a significant effect on organoleptic quality. Steamed brownies have a softer texture, while baked produce a stronger aroma and flavor. The 50:50 ratio achieves the best balance across all sensory metrics.